Comprehension-Based Informed Consent Efficacy in High-Risk Surgeries: A Structural Equation Modeling Study Among Indonesian Patients in a Collectivistic Cultural Context - Mustafa Mahmud; Cinthya Callathea; Yi-Fen Huang; Delia Tamim (Sriwijaya Journal of Forensic and Medicolegal, 2025)
Introduction: Comprehension-based informed consent (IC) represents the ethical and medicolegal foundation of surgical practice, yet its adequacy in collectivistic societies remains insufficiently studied. This study evaluated IC efficacy among high-risk surgical patients in an Indonesian tertiary hospital and identified sociodemographic, psychosocial, and clinical determinants using binary logistic regression within a structural equation modeling (SEM) analytical framework. Methods: A cross-sectional study enrolled 320 adult patients undergoing high-risk elective surgery (cardiac, thoracic, major abdominal, and orthopaedic) at Private Hospital X, Palembang, South Sumatra, Indonesia, from January to December 2024. Validated instruments assessed IC Comprehension Score (ICCS), Health Literacy Level (HLL), Surgeon Communication Quality (SCQ), Family Influence Score (FIS), Collectivism Index (CI), and IC Efficacy Score (ICE, 0–100). Adequate IC efficacy was defined as ICE ≥ 70. Bivariat analysis used Chi-Square and Mann-Whitney U tests. Multivariable binary logistic regression was performed with all continuous predictors standardised. Results: Mean ICCS was 49.4 ± 20.0 and mean ICE was 40.5 ± 19.8. Only 19 participants (5.9%) achieved adequate IC efficacy. Education level was significantly associated with IC efficacy adequacy (χ²=58.9, p<0.001). Spearman correlations revealed strong positive associations between ICCS and ICE (rho=0.773, p<0.001) and HLL and ICE (rho=0.566, p<0.001), and a weak negative association between FIS and ICE (rho=−0.139, p=0.012). In multivariable analysis, ICCS was the sole statistically significant independent predictor of adequate IC efficacy (OR=13.75, 95% CI [3.32–56.92], p<0.001); the model explained 55.4% of variance (Nagelkerke R²=0.554). Conclusion: Comprehension-based IC efficacy is markedly insufficient in this high-risk surgical collectivistic setting, with only 5.9% achieving adequacy. IC Comprehension Score was the sole independent determinant of IC efficacy, underscoring the imperative for structured, comprehension-focused, and culturally tailored IC interventions in Indonesian and comparable surgical settings.